2006
DOI: 10.1097/00001888-200604000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preclinical Preceptorships on Learning the Fundamentals of Clinical Medicine and Physical Diagnosis Skills

Abstract: Preliminary evidence indicates that a short preclinical primary care preceptorship can help medical students to consolidate and integrate the fundamental cognitive and clinical skills they will apply during the clinical years of medical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The multiple logistic regression model was created in a user defined fashion using independent variables that we hypothesized might be associated with receiving higher evaluation scores for teaching clinical skills. These variables included: rank (as a proxy for years of teaching experience), 9,10 department/division, 11 We performed a similar analysis with the mean summary evaluation score as a continuous variable using multiple linear regression. The findings in these 2 regressions were similar (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple logistic regression model was created in a user defined fashion using independent variables that we hypothesized might be associated with receiving higher evaluation scores for teaching clinical skills. These variables included: rank (as a proxy for years of teaching experience), 9,10 department/division, 11 We performed a similar analysis with the mean summary evaluation score as a continuous variable using multiple linear regression. The findings in these 2 regressions were similar (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early clinical exposure can ease a smoother transition from basic science years to the clinical years, the third and fourth years (6). Nieman et al found that students who had early clinical exposure performed better on both a practical physical diagnosis examination and a test of knowledge of clinical medicine when compared to students who did not have clinical exposure during preclinical years (7).…”
Section: Discussionmentioning
confidence: 99%
“…Most US medical schools provide students opportunities for clinical experience in the pre-clerkship curriculum (Lam et al 2002;Nieman et al 2006). These experiences include preceptorships in ambulatory settings, short immersions in inpatient settings, student-run clinics for underserved populations, and shadowing women through pregnancy and delivery.…”
Section: Introductionmentioning
confidence: 99%